2018
DOI: 10.1186/s12905-018-0549-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human-papillomavirus testing and visual inspection for cervical cancer screening in Rwanda

Abstract: BackgroundA pilot screening campaign in Rwanda, based on careHPV-testing followed by visual inspection with acetic acid triage (careHPV+VIA triage), was evaluated against other WHO-recommended screening options, namely HPV screen-and-treat and VIA screen-and-treat.Methods764 women aged 30-69 underwent at visit 1: i) VIA, and cervical cell collection for ii) careHPV in Rwanda, and iii) liquid-based cytology and GP5+/6+ HR-HPV PCR in The Netherlands. All 177 women positive by VIA, careHPV and/or PCR were recalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
(50 reference statements)
3
20
0
Order By: Relevance
“…Self‐collected samples can be more easily obtained in hard‐to‐reach populations (e.g., younger women and those who will not attend screening programs) . Furthermore, HPV DNA testing has higher detection sensitivity as compared with visual inspection with acetic acid (VIA), the national strategy adopted for cervical cancer screening in Mozambique . Therefore, HPV DNA testing might be a better primary screening method for cervical cancer prevention in low‐resource countries …”
Section: Introductionmentioning
confidence: 99%
“…Self‐collected samples can be more easily obtained in hard‐to‐reach populations (e.g., younger women and those who will not attend screening programs) . Furthermore, HPV DNA testing has higher detection sensitivity as compared with visual inspection with acetic acid (VIA), the national strategy adopted for cervical cancer screening in Mozambique . Therefore, HPV DNA testing might be a better primary screening method for cervical cancer prevention in low‐resource countries …”
Section: Introductionmentioning
confidence: 99%
“…Screening with VIA is still the most cost-effective and efficient method of cervical cancer screening in resource-poor countries, however, because it is highly subjective and dependent on training and continued supervision, sensitivity in detecting grade 2 or higher lesions has been reported anywhere from 7.7% to 82.6% compared to care HPV, a low-cost same day testing that has sensitivities above 70%. Screening for HPV offers a more objective approach, and an opportunity to increase screening coverage through self-collection [32,33].…”
mentioning
confidence: 99%
“…Other studies reported similar results with 79% sensitivity and 89% specificity in Africa and India [30], 83% sensitivity and 89% specificity in Mongolia [31], 73% sensitivity and 80% specificity in Kenya [32]. Nevertheless other studies obtained contrasting results with a low sensitivity and high specificity in Rwanda (41% Sensitivity and 96% specificity), [33] or a moderate sensitivity with high specificity in Thailand (67.9% sensitivity and 100% specificity) [34]. This considerable variation between studies on the accuracy of VIA in the detection of high-grade lesions (CIN2 +) is possibly attributable to inter-observer variation, skill levels, light used and acetic acid concentration [35] .In our study, as there was only one observer previously trained in visual screening and colposcopy (2 years) that could explain the 100% sensitivity.…”
Section: Discussionmentioning
confidence: 64%